PENGENDALIAN USAHA MINI MARKET OLEH PEMERINTAH KABUPATEN KLUNGKUNG MELALUI INSTRUMEN PERIJINAN - Arya Tubwana, I Gede; Arya Utama, I Made; Dahana, Cokorda Dalem (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 01, Januari 2014, 2014)
This paper is motivated by the existence of governance based on the principle of legality (the written law) which in practice is inadequate. This is because the law is written always contain weaknesses. Although the principle of legality has weaknesses, he remains a key principle in any law of the State. As with any policy of mini markets trading business needs to be organized with a strong legal basis. In regard to controlling Trading License (License), Local Government Klungkung No. 9 of 2004 on Trade Permit (License). The formulation of the problem in this study: 1) whether the required permissions Klungkung regency governments in controlling the establishment of a mini market in the region. 2) what legal action by the government against the violation of the district Klungkung mini market business license. Results of this study concluded that 1) efforts to establish a market in Klungkung regency min required to have a Business License with the form requirements must be signed by the owner of the company with a complete document specified. 2) The sanctions provided in the form of a written warning to revoking SIUP. The method applied in this study is the juridical-empirical approach. Data were analyzed qualitatively that emphasized on understanding and then compared with the data obtained in the field through interview techniques.
Keywords: Local Government, Monitoring Permit, Mini Market